A short carbon chain fluorine-containing finishing agent and its preparation and application

By using short-carbon chain fluorine-containing acrylate monomers and non-fluorine monomers and crosslinked monomers for core-shell emulsion polymerization, a carbon six-three anti-solidification agent that does not contain harmful substances is prepared, which solves the problem of poor durability of harmful substances and waterproof and oilproof performance in the existing three-solidification agents, and achieves efficient and environmentally friendly waterproof and oilproof performance.

CN117005198BActive Publication Date: 2025-04-08德雄实业(浙江)有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310958322.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-04-08
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

The existing tri-prevention finishing agents contain harmful substances such as PFOA and PFOS, and their waterproof and oil-proof properties have poor durability, making it difficult to meet environmental protection and performance requirements.

Method used

A short-carbon chain fluorine-containing acrylate monomer, non-fluorine monomer and crosslinked monomer were used for core-shell emulsion polymerization to prepare a carbon six-three anti-practic finishing agent that does not contain non-environmental substances such as PFOS, PFOA, and APEO.

Benefits of technology

This finishing agent significantly improves the waterproof and oil-proof performance and durability of the fabric while not containing harmful substances. It is suitable for ordinary waterproof processing and high oil-proof three-proof finishing, and has both anti-alcohol properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117005198B_ABST
    Figure CN117005198B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water- and oil-repellent finishing agents for fabrics, and particularly relates to a short carbon chain fluorine-containing finishing agent and preparation and application thereof. The finishing agent comprises, by weight, 2-5% of a cationic surfactant, 2-5% of a nonionic surfactant, 5-15% of an acrylate monomer, 15-25% of a short chain fluorine-containing acrylate monomer, 0.1-0.5% of an initiator, and 50-60% of water. Compared with the prior art, the invention starts from C6 short carbon chain perfluoroacrylate, aims at the key problem of how to improve the performance of durable low surface energy, and prepares a long-acting high-performance short carbon chain perfluoroacrylate waterproof and oil-proof agent based on a side chain strengthening orientation technology, which can be applied to the waterproof and oil-proof finishing field of industrial textiles and high-end fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water- and oil-repellent finishing agents for fabrics, and more specifically, to a short-carbon-chain fluorine-containing finishing agent and its preparation and application. Background Art

[0002] At present, functional and environmentally friendly textiles are booming and will become the mainstream of textile products in the new century. As people's awareness of the environment and self-protection increases, the requirements for textiles are gradually expanding from softness and comfort, moisture absorption and breathability to antibacterial hygiene, waterproof, oil-proof and anti-fouling, ironing and wrinkle-proof, radiation-proof, UV-proof, flame retardant, medical protection, etc. The development and application of various new fibers and the development of new processes and technologies have gradually realized these requirements, and functional finishing is being driven by the growing demand for high technology and high added value.

[0003] Triple proof finishing refers to multifunctional finishing such as water repellent, oil repellent, and anti-fouling. Triple proof finishing agents refer to textile finishing agents applied to fabrics such as cotton, wool, silk, chemical fiber, and blended fibers, which can change their surface properties and make the fabrics less likely to be wetted or stained by water and common oils and dirt. There are many types of triple proof finishing agents, such as: C8 single waterproof, C8 triple proof finishing agent, C6 single waterproof, and C6 triple proof finishing agent. Although the octafluoro finishing agent has a good effect, it contains harmful substances such as perfluorooctanoic acid ammonium (hereinafter referred to as PFOA) and perfluorooctane sulfonate (hereinafter referred to as PFOS). Therefore, the use of this type of finishing agent has been restricted worldwide.

[0004] Under the guidance of the U.S. Environmental Protection Agency (EPA), 3M began to phase out the production of PFOS, PFOA, their precursors and related compounds in 2000. The fluoropolymer industry signed an agreement with the U.S. EPA to phase out the production of PFOA in 2015. In August 2020, the European Union issued the G / TBT / N / EU / 731 notification, announcing the draft amendment to the REACH regulation, restricting the production and release of longer fluorocarbon chains (perfluorocarboxylic acids containing 9 to 14 carbon atoms), their salts and related substances in the EU. The draft requires that C9-C14 perfluorocarboxylic acids and their salts shall not be used or placed on the EU market when they are components of another substance, in a mixture or in an article, with a total concentration greater than or equal to 25ppb, or when the total concentration of C9-C14 perfluorocarboxylic acid-related substances is greater than or equal to 260ppb. The recently released 2020 version of Oeko-tex standard 100 limits the content of perfluorooctanoic acid (PFOA) and its salts to 0.025ug / m2.

[0005] The environmentally friendly hexacarbon waterproof and oil-proof finishing process is developed in response to market requirements and corresponding environmental regulations. Compared with traditional eight-carbon waterproofing agents, hexacarbon waterproofing agents do not contain banned substances such as PFOS, PFOA, APEO, formaldehyde, etc., are easier to degrade, and are environmentally friendly.

[0006] There are very few domestic manufacturers of short-chain fluorinated acrylate three-proof finishing agents. The technology for producing fluorinated short-chain water-repellents is mainly monopolized by a few foreign companies such as Daikin, Asahi Glass, 3M, DuPont, and Archroma. Due to the complex process technology for producing such products, domestic production has just started, and the waterproof and oil-proof agents that truly belong to our own intellectual property rights are not yet mature. More than 90% of the products in the huge market demand rely on imports. Most domestic research is still in the laboratory and theoretical research stage, and there is still some distance from commercialization.

[0007] Li Xiaowei from Donghua University used homemade N-propyl-N-hydroxyethyl perfluorohexyl sulfonic acid amine as raw material, synthesized a perfluorinated short carbon chain acrylate monomer, N-propyl perfluorohexyl sulfonic acid aminoethyl acrylate (C6F13SO2N(C3H7)CH2CH2OCOCH=CH2) through alcoholysis reaction, and emulsified the obtained fluorinated monomer with octadecyl acrylate and 2-hydroxyethyl acrylate to obtain a fabric finishing agent. It was then applied to pure cotton fabrics, with a finishing agent concentration of 60g / L, a baking temperature of 160℃, and a baking time of 120S. The treated pure cotton fabric had a contact angle of 138.5° to water, an oil repellency grade of 4, and excellent water washability.

[0008] Qian Haihong from Jiangnan University used four carbon short-chain fluorinated monomers, octadecyl acrylate (SA) and butyl acrylate (BA) as the basic monomers, glycidyl methacrylate (GMA) as the cross-linking monomer, and the co-emulsifier dodecanethiol (SH) and the compound emulsifier hexadecyltrimethylammonium bromide (CTAB) and polyoxyethylene lauryl ether system to prepare a quaternary fluorinated acrylate copolymer miniemulsion. The finishing agent was used to finish cotton fabrics, and the contact angle of cotton fabrics to hexadecane was 153.6°, the contact angle to hexadecane was 123.7°, the water repellency level was 5, and the oil repellency level was 3.

[0009] Li Lixin uses NT-X hexafluorocarbon water- and oil-repellent finishing agent from Nano-Tex Company abroad to finish pure cotton, polyester woven fabrics, and nylon woven fabrics. The treated fabrics can maintain a good feel and have advantages in water- and oil-repellency, washability, abrasion resistance, and corrosion resistance.

[0010] Zhejiang Juhua Group began to study C6 and C9 fluorinated finishing agents to replace C8-based fluorinated finishing agents in 2004. However, the final product of the preparation of perfluoroalkyl compounds by telomerization is a mixture of different carbon chains with a wide carbon chain distribution. It is difficult to control the reaction conditions to ensure that the reaction is terminated within the required carbon chain range, but it is still a direction for replacement.

[0011] The mechanism of action of the waterproof and oil-proof agent is to form a thin film on the outer surface of the substrate. The surface tension of the film is lower than that of ordinary liquids, thus showing water-repellent, oil-repellent and anti-fouling functions. The low surface energy of the fluorine-containing polymer itself is the reason for the low surface tension of the film. At the same time, according to the principle of surface physics and chemistry, the surface layer of the film is in contact with the outside world, and its interaction with the outside world determines the size of the surface tension, while the other parts of the film except the surface layer have little effect on the surface tension. Therefore, in the waterproof and oil-proof agent film, only the fluorine-containing polymer is needed to form the surface layer to obtain low surface energy and obtain satisfactory treatment effects. Under this condition, if the other parts of the film do not contain fluorine, the use of fluorine-containing (meth) acrylate monomers can be reduced. In addition, due to the high price of fluorine-containing (meth) acrylate monomers, pollution and energy consumption in the production process, it is necessary to minimize its use.

[0012] Core-shell emulsion technology can make the composition of the latex particle shell polymer different from that of the core polymer through particle design. After film formation, the shell layer is in the outer layer of the film in contact with the outside world, and the core is in the inner layer combined with the textile. The concentration of fluorinated (meth) acrylate monomer in the core is significantly lower than that in the shell layer, or even not added, so that the amount of fluorinated (meth) acrylate monomer can be reduced. There are many literatures and patents published in this regard, but there are more or less the following deficiencies:

[0013] 1. Although some existing finishing agent emulsions use a synthetic process that enriches the fluorinated methacrylate monomer in the shell layer, the hydrophilicity of the shell layer is much lower than that of the core part, and there is a phase inversion during the synthesis and storage process, which affects its use effect; during the production process of these emulsions, although the core-shell morphology can be stabilized by cross-linking, it will also affect the enrichment of the fluorinated polymer in the surface layer when the finishing agent is formed into a film;

[0014] 2. The durability of the existing finishing agents’ waterproof and oil-proof properties is poor. First, the waterproof and oil-proof agents have poor bonding strength with fibers, especially textiles with cotton components. Second, most existing technologies prepare emulsions and then add bridging agents to obtain durability on fabrics. From the perspective of practical use, such designs cannot meet the needs. Summary of the invention

[0015] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a short carbon chain fluorine-containing finishing agent and its preparation and application for solving the above technical problems.

[0016] To achieve the above object, the present invention provides the following technical solutions:

[0017] A short carbon chain fluorine-containing finishing agent, characterized in that it comprises, by weight

[0018] 2-5% cationic surfactant,

[0019] 2-5% nonionic surfactant,

[0020] 5-15% acrylate monomer,

[0021] 15-25% short chain fluorinated acrylate monomer,

[0022] 0.1-0.5% initiator, and

[0023] 50-60% water.

[0024] Furthermore, the cationic surfactant is one or more of octadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, and dodecyltrimethylammonium chloride.

[0025] Furthermore, the nonionic surfactant is fatty alcohol polyoxyethylene ether.

[0026] Furthermore, the acrylate monomer is one or more of octadecyl methacrylate, 4-biphenylmethanol acrylate, and hydroxyethyl methacrylate.

[0027] Furthermore, the acrylate monomer can also be one or more of 2-phenoxyethyl acrylate, 2-phenoxyethyl methacrylate, benzyl acrylate, benzyl methacrylate, isobornyl acrylate, isobornyl methacrylate, lauryl acrylate, lauryl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, stearic acid ester, behenyl acrylate, and behenyl methacrylate.

[0028] Furthermore, the short-chain fluorinated acrylate monomer has the general formula C n F 2n+1 C2H4OCOCR=CH2, where

[0029] R is selected from C1~C2 alkyl; n is 4, 5 or 6.

[0030] Furthermore, the initiator is one of azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, potassium persulfate, sodium persulfate and ammonium persulfate.

[0031] A method for preparing a short carbon chain fluorine-containing finishing agent comprises the steps of:

[0032] S1, mixing a cationic surfactant, a nonionic surfactant, an acrylate monomer, a short-chain fluorinated acrylate monomer and water, and emulsifying them with a homogenizer to obtain a pre-emulsion;

[0033] S2, nitrogen is passed through the pre-emulsion for 30 minutes, heated to 50-80 degrees Celsius, and an aqueous solution of the initiator is added dropwise under nitrogen protection, and the reaction is kept warm for 2-6 hours;

[0034] S3, cooling to 20-25°C to obtain a finishing agent.

[0035] Furthermore, the fluorine-containing finishing agent is used as a fabric waterproof finishing agent.

[0036] The method for using the fluorine-containing finishing agent comprises the following steps:

[0037] Ⅰ. Prepare working solution: 30g / L-50g / L,

[0038] Ⅱ. Finishing on fabric: Use padding method, one dip and one pad, with a liquid rate of 30-40%.

[0039] III. Baking: Bake at 160-180℃ for one minute.

[0040] By adopting the above technical solution, the beneficial effects of the present invention are:

[0041] 1. The present invention uses perfluorohexyl acrylate monomer, non-fluorine monomer and non-fluorine crosslinking monomer as raw materials, adopts core-shell emulsion polymerization method, uses cationic-nonionic composite surfactant as emulsifier, and prepares fluorine-containing waterproof finishing agent in semi-continuous feeding mode;

[0042] 2. Compared with general C6 waterproofing agents, this product has a wider adaptability to fabrics. It can not only meet the requirements of ordinary waterproof processing, but also is suitable for high oil-proof three-proof finishing, and also has alcohol-proof performance;

[0043] 3. Compared with the traditional carbon eight waterproofing agent, the carbon six three-proof finishing agent of the present invention does not contain non-environmentally friendly substances such as PFOS, PFOA, APEO, etc., and can meet the processing requirements of carbon six environmentally friendly waterproofing orders at home and abroad. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a line graph of the emulsion conversion rate and emulsion gel rate of the emulsion at different emulsifier concentrations of the examples of the present invention.

[0045] Figure 2 It is a line graph of the emulsion conversion rate and emulsion gel rate of the emulsion at different concentrations of the fluorinated monomer of the embodiment of the present invention.

[0046] Figure 3 It is a line graph of the emulsion conversion rate and emulsion gel rate of the emulsion at different concentrations of the functional monomer of the embodiment of the present invention.

[0047] Figure 4 It is a line graph of the emulsion conversion rate and emulsion gel rate of the emulsion at different concentrations of the cross-linking monomer of the embodiment of the present invention.

[0048] Figure 5 The present invention is a flow chart of the preparation process of an embodiment of the present invention.

[0049] Figure 6 It is a schematic diagram of the reaction equation of the hexacarbon waterproofing agent of the present invention.

[0050] Figure 7 Schematic diagram of particle size distribution of the finishing agent of the present invention. DETAILED DESCRIPTION

[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0053] The short carbon chain fluorine-containing finishing agent of the present invention is prepared by using perfluorohexylethyl acrylate monomer (C6F), non-fluorine monomers (octadecyl methacrylate (SMA), 4-biphenylmethanol acrylate (BPMA)) and non-fluorine crosslinking monomers (hydroxyethyl methacrylate (HEMA)) as raw materials, adopting a core-shell emulsion polymerization method, using a cationic-nonionic composite surfactant as an emulsifier, and a semi-continuous feeding method. The specific implementation process is as follows:

[0054] The amount of emulsifier and monomer used in the core-shell emulsion polymerization process will have a great influence on the stability of the emulsion and the water and oil repellency effect, so it is necessary to determine the emulsifier and monomer conditions of the emulsion polymerization reaction.

[0055] 1. Selection of emulsifier

[0056] Emulsifiers are usually divided into two types: nonionic and ionic. If only one type of emulsifier is used, the emulsion system is very unstable, prone to demulsification and stratification, and even precipitation. Therefore, the use of nonionic emulsifiers or ionic emulsifiers can not only improve the emulsification effect, but also maintain the stability of the emulsion to achieve a synergistic effect; in addition, adding nonionic emulsifiers to the emulsification system can significantly reduce the charge density on the surface of the monomer droplets, making it easier for free radicals to enter the droplets, thereby increasing the polymerization reaction rate.

[0057] 2. Selection of emulsifier dosage

[0058] The raw material mass ratio was fixed as follows: C6F: SMA: BPMA: HEMA = 12: 10: 3: 1, the initiator azobisisobutylamidine hydrochloride was 0.8% of the monomer mass, the reaction temperature was 70°C, the reaction time was 4h, and the polymerization reaction was carried out at different emulsifier concentrations; the prepared emulsion was evaluated by emulsion conversion rate and gel rate to determine the effect of emulsifier dosage on emulsion polymerization. The experimental results are shown in Figure 1 shown.

[0059] from Figure 1 It can be seen that when the amount of emulsifier is small, the monomer conversion rate is low and the gel rate is high. As the amount of emulsifier increases, the conversion rate increases and the gel rate decreases. This is because as the amount of emulsifier increases, more emulsifier covers the surface of the monomer droplets, avoiding the collision of small droplets to form large droplets, reducing the occurrence of gel rate. At the same time, the emulsifier can also reduce the particle size of the monomer droplets dispersed in the system, increase the specific surface area, increase the reaction site, and the monomer can be fully polymerized, thereby improving the monomer conversion rate.

[0060] When the emulsifier concentration reaches more than 6%, the monomer conversion rate decreases with the increase of emulsifier dosage; the increase of emulsifier dosage increases the sites of polymerization reaction and prolongs the life of free radicals, so the conversion rate gradually increases, but too much emulsifier dosage will make the emulsion very sticky, the molecular chains will be entangled together, the gel will increase, the stability will decrease, and it will affect the diffusion of monomers and reduce the monomer conversion rate; therefore, the dosage of mixed emulsifier is selected to be 6%.

[0061] 3. Selection of the dosage of fluorinated monomers

[0062] In the emulsion polymerization reaction, the fluorinated monomer is the most important one among all the components. The amount of fluorinated monomer used will directly affect the water and oil repellency of the finishing agent, and the price of fluorinated monomer is quite high. Excessive use of this type of monomer will inevitably increase the price of the final product. However, through the core-shell emulsion polymerization technology, the fluorinated monomer is polymerized on the shell, so that it is mainly enriched on the surface of the film during the film formation process, thereby effectively changing the surface properties of the polymer without significantly increasing its cost.

[0063] The raw material mass ratio was fixed as follows: SMA: BPMA: HEMA = 10: 3: 1, the initiator azobisisobutylamidine hydrochloride (AIBA) was 0.8% of the monomer mass, the composite emulsifier concentration was 6%, the reaction temperature was 70°C, the reaction time was 4h, and the polymerization reaction was carried out at different fluorinated monomer concentrations. The prepared emulsion was evaluated by emulsion conversion rate and gel rate to determine the effect of fluorinated monomer dosage on emulsion polymerization. The experimental results are shown in Figure 2. Figure 2 shown.

[0064] from Figure 2 It can be seen that with the increase of the amount of fluorinated monomer, the conversion rate and gel rate do not change much, but when the amount of fluorinated monomer exceeds 14%, the conversion rate and polymerization stability are reduced; this is because the side chain of the polymer is a longer fluorinated monomer with stronger hydrophobicity. When the amount of fluorinated monomer is low, the diffusion of monomer droplets in the aqueous phase can still proceed smoothly, but when the monomer concentration increases to a certain level, the strong hydrophobicity of the fluorinated monomer causes the instability of the polymerization reaction, resulting in a decrease in the conversion rate and an increase in the gel rate; therefore, the amount of fluorinated monomer is selected to be 14%.

[0065] 4. Optimal dosage of functional monomers

[0066] Based on the side chain enhanced orientation technology, the fluorinated monomer is copolymerized with 4-biphenylmethanol acrylate. The rigid biphenyl group strengthens the orientation of the fluorinated carbon chain segment, inhibiting its retreat back to the polymer body during contact with water, greatly improving the dynamic water repellency, and can improve the waterproof and oil-proof performance of the finishing agent.

[0067] The raw material mass ratio was fixed: C6F: SMA: HEMA = 14: 10: 1, the initiator azobisisobutylamidine hydrochloride (AIBA) was 0.8% of the monomer mass, the composite emulsifier concentration was 6%, the reaction temperature was 70°C, the reaction time was 4h, and the polymerization reaction was carried out at different 4-biphenylmethanol acrylate (BPMA) monomer concentrations. The prepared emulsion was evaluated by emulsion conversion rate and gel rate to determine the effect of fluorinated monomer dosage on emulsion polymerization. The experimental results are shown in Figure 3 shown.

[0068] from Figure 3 It can be seen that the amount of functional monomer added is small, which has little effect on the overall conversion rate of the polymer reaction. When the amount of functional monomer is 4%, the gel begins to rise and the amount of gel increases. This may be because the functional monomer has strong hydrophobicity and low solubility in water, which can easily cause system instability and easily produce gel during the polymerization process, thus affecting its application performance. Therefore, the optimal amount of functional monomer is 4%.

[0069] 5. Optimal Amount of Cross-linking Monomer

[0070] Hydroxyethyl methacrylate (HEMA) is used as the crosslinking agent monomer. This monomer contains two active groups, which can not only participate in polymerization, but also undergo crosslinking reaction with the matrix, so that the polymer chain segments form covalent bonds with the fibers, increasing fastness and improving wash resistance.

[0071] The raw material mass ratio was fixed as follows: C6F: SMA: BPMA = 14: 10: 4, the initiator azobisisobutylamidine hydrochloride (AIBA) was 0.8% of the monomer mass, the composite emulsifier concentration was 6%, the reaction temperature was 70°C, the reaction time was 4h, and the polymerization reaction was carried out at different cross-linking monomer concentrations. The prepared emulsion was evaluated by emulsion conversion rate and gel rate to determine the effect of cross-linking monomer dosage on emulsion polymerization. The experimental results are shown in Figure 2. Figure 4 shown.

[0072] from Figure 4 It can be seen that the amount of cross-linking monomer added is relatively small, which has little effect on the overall conversion rate and gel rate of the polymer reaction.

[0073] As a cross-linking monomer, hydroxyethyl methacrylate mainly covalently bonds with the fiber through "-OH" to form a network cross-linking structure, tightly and orderly fixes the fluorinated chain segments on the fabric surface, inhibits the rearrangement of the fluorinated chain segments, and improves the water and oil repellency of the fabric; however, when the amount of cross-linking monomer is too much, it will lead to too many hydrophilic groups in the polymer macromolecule. Although the degree of cross-linking with the fabric is increased, the attachment of polar groups on the fiber surface increases its hydrophilicity and reduces the water and oil repellency. Therefore, after comprehensive consideration, 1.0% of hydroxyethyl methacrylate is selected.

[0074] 6. Preparation process of finishing agent

[0075] Based on the results of the above steps, Figure 5 The preparation is carried out according to the preparation process route shown.

[0076] Pre-emulsification of seed emulsion: first add core monomers (octadecyl methacrylate (SMA), 4-biphenylmethanol acrylate (BPMA), hydroxyethyl methacrylate (HEMA)) and shell monomers (perfluorohexylethyl acrylate (C6F), octadecyl methacrylate (SMA), 4-biphenylmethanol acrylate (BPMA), hydroxyethyl methacrylate (HEMA)) into 1 / 3 of the designed mass of emulsifier solution, pre-emulsify for 1 hour to obtain a pre-emulsion.

[0077] Synthesis of core-shell copolymer emulsion: Into a 500mL four-necked round-bottom flask equipped with a thermometer, electric stirrer, nitrogen introduction device and reflux condenser, nitrogen was introduced to exclude oxygen, and the remaining 1 / 3 of the emulsifier aqueous solution, 1 / 2 of the core monomer pre-emulsion, and 1 / 3 of the initiator azobisisobutylamidine hydrochloride were added in sequence. After stirring and mixing evenly, the temperature was raised to 70°C for polymerization and the reaction was carried out for 20-30 minutes. The remaining core monomer and 1 / 3 of the initiator solution were slowly dripped into the dropping funnel to obtain the seed core emulsion.

[0078] In the seed core emulsion, keep warm for 30 minutes, and then drip the shell monomer pre-emulsion and the remaining 1 / 3 initiator solution through a dropping funnel. Finally, start the timing while keeping warm, and end the reaction when the designed reaction time is reached. After the reaction is completed, cool it naturally to room temperature, stop stirring, and then filter and discharge to obtain the hexacarbon waterproofing agent emulsion; its specific reaction equation is as follows Figure 6 shown.

[0079] Through the above preparation process and expanding the production capacity, the test data of the C6 waterproofing agent emulsion is shown in the following table;

[0080] project Test conditions index Batch 1 Batch 2 Batch 3 Appearance Test tube method Milky white lotion qualified qualified qualified Water Solubility Open dilution method No sediment, no floating objects qualified qualified qualified density Density cup, 23±2℃ <![CDATA[1.04-1.14g / cm 3 ]]> 1.06 1.07 1.06 pH pH Meter 2.5±1.0 2.68 2.90 2.75 Solid content 105℃×3h 34±1% 33.52% 34.39% 34.14% Gel rate Filter weighing Below 1.5% 0.45% 0.37% 0.39% Yield Weight calculation More than 95% 96.51% 97.84% 98.29%

[0081] Product stability

[0082] C6 waterproofing agent Test conditions Batch 1 Batch 2 Batch 3 Storage stability Sealed and stored for 6 months Unstratified precipitation Unstratified precipitation Unstratified precipitation Mechanical stability Speed ​​2000r / min, centrifugation 10 min Unbroken emulsion Unbroken emulsion Unbroken emulsion Dilution stability Dilute 5, 10, 100 times and store for 7 days Unstratified precipitation Unstratified precipitation Unstratified precipitation Weathering stability Low temperature resistance -5℃×7d, high temperature resistance 60℃×48h Unstratified precipitation Unstratified precipitation Unstratified precipitation

[0083] It can be seen from the above table that the storage stability, mechanical stability, dilution stability and weathering stability of the C6 waterproofing agent emulsion are all good, indicating that the synthesized emulsion sample has good stability and is easy to store and use.

[0084] 7. Particle size analysis of emulsion

[0085] The particle size and distribution of the emulsion are important technical indicators of polymer emulsion, which will directly affect the application performance of the carbon six water repellent finishing agent emulsion on fabrics. The particle size distribution was measured using a nanometer particle size and potential analyzer. The results are as follows: Figure 7 shown.

[0086] Depend on Figure 7 It can be seen that the particles of the C6 waterproofing agent emulsion are mainly distributed between 70-130nm, with an average particle size of 110nm, which shows that the C6 waterproofing agent emulsion is monodisperse, and the distribution area is very narrow, without large particles agglomeration, indicating that this emulsion has good stability.

[0087] 8. Application of finishing agent

[0088] The carbon six water-proof and oil-proof finishing agent of the present invention is not only suitable for synthetic fiber fabrics, but also can be applied to water-proof and oil-proof finishing of natural fiber fabrics and blended fabrics thereof. The finishing agent contains an internally added crosslinking agent, which can give the fabrics good water-proof and oil-proof durability and improve the washability and wearability. At the same time, it can be processed with other post-finishing agents, shortening the process and flow for manufacturers, saving production costs, and improving the cost performance of products.

[0089] The carbon six water-proof and oil-proof finishing agent emulsion prepared under the optimal synthesis process conditions was applied to the water- and oil-repellent finishing of chemical fiber fabrics (polyester taffeta, nylon taffeta) and natural fiber fabrics (pure cotton twill). By comparing with similar carbon six water-proof agents on the market, the water-proof and oil-proof properties, as well as the properties after using stiffeners, softeners and antistatic agents were tested.

[0090] The initial waterproof and oil-proof performance test results are as follows:

[0091] 1. Water repellency: measured according to AATCC 22-2017 standard;

[0092] 2. Oil repellency: measured according to AATCC 118-2007 standard;

[0093]

[0094] Waterproof and oil-proof washability test (home washing 10 times, 20 times):

[0095]

[0096] Performance test of waterproofing agent combined with other functional additives:

[0097]

[0098] By comparison, it can be seen that the performance of this finishing agent has surpassed the commercially available C6 waterproof agent and has higher waterproof and oil-proof properties.

[0099] The present invention has been tested by the Quality Supervision and Inspection Center, as shown in the following table:

[0100] Application process Suitable for padding and shaping processing Solid content 34±1% Main Ingredients Fluorocarbon copolymers pH 2.5±1.0 Ionic Weak cation Solubility Dilute with water in any proportion Waterproof performance on cotton (30g / L) 90 points Oil resistance on cotton (30g / L) Level 6 Polyester cotton waterproof performance (30g / L) 90-100 points Polyester cotton oil resistance (30g / L) Level 6

[0101] From the above table, we can see that the performance of this product has reached a relatively advanced technical level.

[0102] The invention prepares a hexacarbon water-proof and oil-proof finishing agent copolymer emulsion with a core-shell structure by a semi-continuous feeding method, and adopts different types of emulsifiers to compound nonionic emulsifiers and cationic emulsifiers in proportion, so that the emulsion polymerization process is stable, the emulsion has good shear resistance, thinning stability and storage stability, and is convenient for factory mass production;

[0103] Through the side chain enhanced orientation technology, the fluorocarbon chain segment orientation is introduced to enhance the arrangement, thereby improving the waterproof and oil-proof performance of the finishing agent; the cross-linking monomer is introduced to form a covalent bond between the waterproofing agent polymer segment and the fiber, thereby increasing the fastness and improving the washing resistance; through this series of monomer improvements, the original characteristics of the hexacarbon waterproofing agent are maintained and the overall waterproof and wash resistance is improved.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Common changes and substitutions made by those skilled in the art within the scope of the technical solution of the present invention should be included in the protection scope of the present invention.

Claims

1. A short carbon chain fluorine-containing finishing agent, characterized in that: Included by weight 2-5% cationic surfactant, 2-5% nonionic surfactant, 5-15% acrylate monomer, 15-25% short chain fluorinated acrylate monomer, 0.1-0.5% initiator, and 50-60% water; The acrylate monomer is one or more of octadecyl methacrylate, 4-biphenylmethanol acrylate, and hydroxyethyl methacrylate, and the initiator is azobisisobutyramidine hydrochloride; The general formula of short-chain fluorinated acrylate monomer is CnF2n+1C2H4OCOCR=CH2, where: R is selected from C1~C2 alkyl; n is 4, 5 or 6; The preparation method of the carbon chain fluorine-containing finishing agent comprises the steps of: S1, mixing a cationic surfactant, a nonionic surfactant, an acrylate monomer, a short-chain fluorinated acrylate monomer and water, and emulsifying them with a homogenizer to obtain a pre-emulsion; The method comprises the following steps: firstly mixing a cationic surfactant, a nonionic surfactant and water to form an emulsifier solution, and then adding an acrylate monomer and a short-chain fluorinated acrylate monomer to the emulsifier solution with a mass of 1 / 3, respectively, and pre-emulsifying for 1 hour to obtain a core monomer pre-emulsion and a shell monomer pre-emulsion; S2, nitrogen is passed through the pre-emulsion for 30 minutes, heated to 50-80 degrees Celsius, and an aqueous solution of the initiator is added dropwise under nitrogen protection, and the reaction is kept warm for 2-6 hours; Wherein, nitrogen is introduced into the flask to exclude oxygen, and the remaining 1 / 3 of the emulsifier aqueous solution, 1 / 2 of the core monomer pre-emulsion and 1 / 3 of the initiator solution are added in sequence, stirred and mixed evenly, and then heated for polymerization, reacted for 20-30 minutes, and then the remaining core monomer pre-emulsion and 1 / 3 of the initiator solution are slowly dropped into the flask to obtain a seed core emulsion; In the seed core emulsion, keep warm for 30 minutes, then drop the shell monomer pre-emulsion and the remaining 1 / 3 initiator solution respectively, and start timing while keeping warm, and the reaction ends when the reaction time is reached; S3, cooling to 20-25°C, after cooling, stopping stirring, filtering and discharging to obtain the finishing agent.

2. A short carbon chain fluorine-containing finishing agent according to claim 1, characterized in that: The cationic surfactant is one or more of octadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and dodecyltrimethylammonium chloride.

3. A fluorine-containing finishing agent according to claim 1, characterized in that: The nonionic surfactant is fatty alcohol polyoxyethylene ether.

4. A short carbon chain fluorine-containing finishing agent according to claim 1, characterized in that: The acrylate monomer may also be one or more of 2-phenoxyethyl acrylate, 2-phenoxyethyl methacrylate, benzyl acrylate, benzyl methacrylate, isobornyl acrylate, isobornyl methacrylate, lauryl acrylate, lauryl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, stearic acid ester, behenyl acrylate, and behenyl methacrylate.

5. A short carbon chain fluorine-containing finishing agent according to claim 1, characterized in that: The initiator may also be one of azobisisobutylimidazoline hydrochloride, potassium persulfate, sodium persulfate and ammonium persulfate.

6. Use of the short carbon chain fluorine-containing finishing agent according to any one of claims 1 to 5 as a fabric waterproof finishing agent.

7. A method for using a short carbon chain fluorine-containing finishing agent according to any one of claims 1 to 5, characterized in that: The following steps are involved: Ⅰ. Prepare working solution: 30g / L-50g / L, Ⅱ. Finishing on fabric: Use padding method, one dip and one pad, with a liquid rate of 30-40%. III. Baking: Bake at 160-180℃ for one minute.

Citation Information

Patent Citations

  • Preparation method of polymer containing short fluorocarbon chain, and preparation method of polymer

    CN107602754A